Incorporating a human rights-based approach to irregular migration: a Chilean case study - Rioseco Vallejos, Valentina (The University of Edinburgh. College of Humamities and Social Sciences, 2026)
This thesis examines whether the domestic incorporation of human rights could support an effective solution to irregular migration. It stems from the recognition that the human rights-based approach to irregular migration is to open diverse and accessible pathways for regular migration. It also identifies a gap in the literature concerning the construction of these pathways to regular migration. Therefore, it uses the methodology of legal and doctrinal analysis to analyse part of the human rights framework protecting the entry of migrants and the obligations emanating from it. It also considers policy arguments and data obtained my civil society organisation. Specifically, it analyses the extent to which the principle of non-discrimination and the principle of non-refoulement protect the entry of migrants into a country that is not their country of origin. The analysis is focused on the interaction of human rights law at three different levels, namely the international level, the regional level and the domestic level. Particularly, it observes the Inter American Human Rights System, which presents a number of distinctive features discussed in later chapters, and focuses on Chile as a case study.
Keywords: irregular migration; human rights law; Chilean migration policy; migration law; ICRMW; ILO Conventions; migrant workers; forced migration; non-refoulement; Inter-American human rights law